2014
DOI: 10.5301/ejo.5000483
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Characteristics of Charles Bonnet Syndrome in Madrid, Spain

Abstract: Purpose Charles Bonnet syndrome (CBS) is a condition characterized by development of visual hallucinations in patients with no cognitive impairment and significant loss of vision mainly caused by age-related macular degeneration (AMD) or glaucoma. Methods This was a study of prevalence and characteristics of CBS diagnosed at the Neuroophthalmic Unit within the Ophthalmology Department of Hospital Clínico San Carlos (HCSC), Madrid, Spain. Results The CBS prevalence in patients from HCSC Madrid is 0.47%, ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
(34 reference statements)
3
14
0
Order By: Relevance
“…The most common conditions associated with CBS are AMD, cataract, glaucoma and DR [23,24]. AMD is by far the most commonly reported ocular disease associated with CBS [5,22,25]. In our study, 70.5% of the patients with CBS had AMD, which was comparable with the literature.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The most common conditions associated with CBS are AMD, cataract, glaucoma and DR [23,24]. AMD is by far the most commonly reported ocular disease associated with CBS [5,22,25]. In our study, 70.5% of the patients with CBS had AMD, which was comparable with the literature.…”
Section: Discussionsupporting
confidence: 81%
“…If the Danish group had excluded all patients with a visual acuity of >0.5 on the better-seeing eye, they would have reached a prevalence rate of 12%. In a study from Spain, the prevalence rate of CBS was 0.47% and increased to 15% when limited to patients with low vision [22]. These findings were similar to the Danish study.…”
Section: Discussionsupporting
confidence: 79%
“…These may be white or coloured, static or animated [4,19]. While some of our patients saw simple shapes, balls, or circles, their other hallucinations were more complex, such as their office or a child.…”
Section: Discussionmentioning
confidence: 99%
“…While the duration is usually less than 12 months, they may persist for several years [4]. Santos Bueso et al reported complex hallucinations that mainly involved people and faces, with movement and colour; their patient had daily episodes lasting between 3 and 5 min that evolved over 6-12 months [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation